Pharmacological management of seizures in patients with COVID-19: a systematic review [version 2; peer review: 2 approved] - Priscilla Kolibea Mante; John-Paul Omuojine; Nana Ofori Adomako; Paulina Antwi (Open Research Africa)
Background: Some patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported to exhibit neurological symptoms such as seizures and impaired consciousness. Our study reviews reported cases to assess the pharmacological approach to managing seizures in SARS-CoV-2 patients and associated outcomes. Methods: A systematic review of case reports on the incidence of seizures following coronavirus disease 2019 (COVID-19) among patients that reported use of antiepileptic drugs (AEDs) in management was performed by using the PRISMA (preferred reporting items for systematic reviews and meta-analysis) guidelines. Databases used included EMBASE, PubMed, SCOPUS, and Google Scholar. Data was presented as qualitative and descriptive data. Results: In total, 67 articles were selected for full-text assessment, of which 18 were included in the final review. Patients had a median age of 54 years, most of whom were male. Remdisivir, dexamethasone, Laninamivir, hydroxychloroquine, azithromycin, and Lopinavir-ritonavir were common agents used in the management of COVID-19. Most patients presented with either generalized tonic-clonic seizures or status epilepticus. Most patients received levetiracetam as drug choice or as part of their regimen. Other AEDs commonly prescribed included midazolam and sodium valproate. Some patients received no antiepileptic drug therapy. Most of the patients who died had more than one comorbidity. Also, most of the patients who died received COVID-19 treatment drugs. None of the patients who received midazolam as drug choice or as part of their regimen developed recurrent seizures in contrast to patients who received levetiracetam and sodium valproate as drug choice or as part of their regimen. Interestingly, none of the patients who received no AEDs suffered recurrent seizures or died. Conclusions: Standard guidelines for managing seizures in COVID-19 patients may be required. A limitation of this review is that it involved the use of case reports with no controls and a small number of patients.